The First Peopling of South America: New Evidence from Y-Chromosome Haplogroup Q - BATTAGLIA, VINCENZA; GRUGNI, VIOLA; TORRONI, ANTONIO; SEMINO, ORNELLA; Perego UA; Angerhofer N; Gomez Palmieri JE; Woodward SR; ACHILLI, ALESSANDRO; Myres N (PLoS ONE, 2013)
Recent progress in the phylogenetic resolution of the Y-chromosome phylogeny permits the male demographic dynamics and migratory events that occurred in Central and Southern America after the initial human spread into the Americas to be investigated at the regional level. To delve further into this issue, we examined more than 400 Native American Y chromosomes (collected in the region ranging from Mexico to South America) belonging to haplogroup Q - virtually the only branch of the Y phylogeny observed in modern-day Amerindians of Central and South America - together with 27 from Mongolia and Kamchatka. Two main founding lineages, Q1a3a1a-M3 and Q1a3a1-L54(xM3), were detected along with novel sub-clades of younger age and more restricted geographic distributions. The first was also observed in Far East Asia while no Q1a3a1-L54(xM3) Y chromosome was found in Asia except the southern Siberian-specific sub-clade Q1a3a1c-L330. Our data not only confirm a southern Siberian origin of ancestral populations that gave rise to Paleo-Indians and the differentiation of both Native American Q founding lineages in Beringia, but support their concomitant arrival in Mesoamerica, where Mexico acted as recipient for the first wave of migration, followed by a rapid southward migration, along the Pacific coast, into the Andean region. Although Q1a3a1a-M3 and Q1a3a1-L54(xM3) display overlapping general distributions, they show different patterns of evolution in the Mexican plateau and the Andean area, which can be explained by local differentiations due to demographic events triggered by the introduction of agriculture and associated with the flourishing of the Great Empires.